ICT for resource management and telematics in construction sites. (2017) - Czart, Wojciech; Gierszal, Henryk; Pawlina, Karina; Urbańska, Maria
Abstract: In the paper we present solutions that can be applied by management staff for online collaboration works and management of resources in construction sites. Such software can be based on a framework of Google applications that offer almost versatile and ubiquitous features for data processing, communication, workflow processing and resource management. They can be used to build an Integrated Collaboration Environment that can run using a cloud computing. Moreover such a solution can be integrated with Internet of Thinks platform to foster monitoring and controlling tasks led by civil engineers to govern quality of construction works.